2021
DOI: 10.1590/1413-81232021264.13862018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HAART in the nutritional status of children and adolescents infected by HIV in Brazil: a systematic review

Abstract: The verification of factors associated with growth, body composition and nutritional and nutritional aspects after HIV infection in children or adolescents in Brazil is fundamental for progress in this area. We selected articles published until 2018, available on the platforms PubMed and Lilacs, using the keywords The following descriptors and their associations were used, extracted from MeSH: “Children”, “Adolescent”, “Anthropometry”, “Nutritional Assessment”, “HIV”, “Brazil” adding the filter “and” for advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(103 reference statements)
0
4
0
1
Order By: Relevance
“…Em crianças com HIV, no estudo de LIMA et al (17) , concluiu em sua amostra que crianças e adolescentes que vivem com o vírus da imunodeficiência humana possuem baixa massa óssea para idade, e o uso de inibidores de protease parece estar relacionado a tais reduções. O que corrobora com Gratão, Nascimento e Pereira (30) , que em um levantamento bibliográfico concordaram que crianças e adolescentes vivendo com HIV apresentam ou podem ter alterações no metabolismo ósseo, de lipídeos e na composição corporal relacionada à infecção ou associadas à terapia. Existem poucas evidencias direcionadas a alterações citopatológicas do vírus HIV.…”
Section: Resultsunclassified
“…Em crianças com HIV, no estudo de LIMA et al (17) , concluiu em sua amostra que crianças e adolescentes que vivem com o vírus da imunodeficiência humana possuem baixa massa óssea para idade, e o uso de inibidores de protease parece estar relacionado a tais reduções. O que corrobora com Gratão, Nascimento e Pereira (30) , que em um levantamento bibliográfico concordaram que crianças e adolescentes vivendo com HIV apresentam ou podem ter alterações no metabolismo ósseo, de lipídeos e na composição corporal relacionada à infecção ou associadas à terapia. Existem poucas evidencias direcionadas a alterações citopatológicas do vírus HIV.…”
Section: Resultsunclassified
“…In children, HIV infection leads to malnutrition, which in turn can lead to growth retardation, although ndings differ widely depending on the geographical area and are more accentuated in middle-and low-income countries [31][32][33][34][35][36] . In our work, 28.3% and 51.1% of children under 5 years of age had, respectively, a weight and height percentile of less than 3 at the rst check-up after diagnosis, with a slight improvement in subsequent check-ups, after several months or years in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1 The World Health Organization (WHO) estimated that, of about 1.7 million children under the age of 15 living with HIV, about 160,000 acquired the virus and 98,000 died from HIV-1-related causes in 2021. 2 The introduction of antiretroviral therapy (ART) showed valuable results in HIV-infected individuals; it reduced morbidity and mortality, reduced the incidence of opportunistic diseases, increased length and quality of life, and improved neural development and linear growth in growing children. [2][3][4][5] Protease inhibitors (PIs), like ritonavir (RTV), darunavir and atazanavir, are well known to cause high triglycerides (TG), high total cholesterol and low high-density lipoprotein cholesterol (HDL-C) levels.…”
Section: Introductionmentioning
confidence: 99%
“…2 The introduction of antiretroviral therapy (ART) showed valuable results in HIV-infected individuals; it reduced morbidity and mortality, reduced the incidence of opportunistic diseases, increased length and quality of life, and improved neural development and linear growth in growing children. [2][3][4][5] Protease inhibitors (PIs), like ritonavir (RTV), darunavir and atazanavir, are well known to cause high triglycerides (TG), high total cholesterol and low high-density lipoprotein cholesterol (HDL-C) levels. 6 It was found that children and adolescents on a lopinavir/ritonavir (LPV/r) regimen had a four times greater chance of presenting with hypercholesterolemia and elevated TG levels when compared to those do not on ART.…”
Section: Introductionmentioning
confidence: 99%